Hubungan Pola Makan dan Pendapatan Keluarga dengan Kejadian Kekurangan Energi Kronis (KEK) pada Ibu Hamil di Wilayah Kerja Puskesmas Kertak Hanyar - Nirma Yunita; Mahrita Ariyati (Jurnal Kesehatan Indonesia, 2021)
Chronic energy deficiency (CED) can occur in women of childbearing age and pregnant women due to several factors (e.g., dietary patterns, economic status, population density, infection, and poverty). The proportion of pregnant women aged 15-19 years with CED increased from 31,3% in 2010 to 38,5% in 2013 in Indonesia. The proportion of non-pregnant women with CED also increased from 30,9% in 2010 to 46,6% in 2013. The risk of CED among pregnant women in South Kalimantan was high. There were five sub-districts/cities with the highest incidence of CED, i.e., Hulu Sungai Utara (29,9%), Balangan (20,4%), Banjar (18,8%), Tanah Laut (17,5%), and Tapin (14,3%). Dietary patterns and family income are factors that may affect the incidence of CED. This study aimed to analyze the relation of dietary patterns and family income to the incidence of CED in pregnant women in the working area of ​​the Puskesmas Kertak Hanyar. This analytical study used a cross-sectional design. A total of 43 pregnant women with CED in the working area of ​​Puskesmas Kertak Hanyar participated in this study. This study’s results were analyzed using the Spearman rho correlation test with a p-value of <0.05. Based on the statistical test results, the dietary patterns of pregnant women had a significant relationship with CED (p=0,001; r=0,475). Family income had a significant relationship with CED (p=0.000; r=0,475) among pregnant women in the working area of ​​the Puskesmas Kertak Hanyar.